1982
DOI: 10.3758/bf03213715
|View full text |Cite
|
Sign up to set email alerts
|

Influence of shock controllability by dominant rats on subsequent attack and defensive behaviors toward colony intruders

Abstract: Thirty colonies, each consisting of a female and two male adult albino rats, remained intact for an a-week period. Naive conspecific intruders were then introduced into each colony for a 10-min test for 5 consecutive days. Videotapes of the tests were scored for aggressive and defensive behaviors. In every colony, aggression was greatest for a single alpha male. The alpha rats were randomly given one of three treatments: wheel-turn escape training, inescapable yoked shock, or restraint without shock. The alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

1984
1984
1996
1996

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Assuming that such changes in affect are transitional, it is conceivable that inescapable shock might later have a significant influence on how a mother rat interacts with her offspring. This argument is, to some degree, consistent with the fact that differential affective states resulting from shock controllability have been observed in terms of the changes in aggressive and defensive behaviors seen when dominant colony males encounter conspecific intruders (Williams, 1982). However, the major weaknesses of the learned-helplessness interpretation are that (1) it does not specify a precise behavioral or physiological mechanism for why inescapable shock produces a deficit in affect, and (2) it fails to describe the boundary conditions or limits of the helplessness effects.…”
Section: Contacts the Difference Between Group Y Andsupporting
confidence: 64%
“…Assuming that such changes in affect are transitional, it is conceivable that inescapable shock might later have a significant influence on how a mother rat interacts with her offspring. This argument is, to some degree, consistent with the fact that differential affective states resulting from shock controllability have been observed in terms of the changes in aggressive and defensive behaviors seen when dominant colony males encounter conspecific intruders (Williams, 1982). However, the major weaknesses of the learned-helplessness interpretation are that (1) it does not specify a precise behavioral or physiological mechanism for why inescapable shock produces a deficit in affect, and (2) it fails to describe the boundary conditions or limits of the helplessness effects.…”
Section: Contacts the Difference Between Group Y Andsupporting
confidence: 64%
“…First, it has been known for some time that the development and maintenance of strong social dominance require that rats reside in mixed-sex cages (e.g., Bamett, 1960;Flannelly,Flannelly,& R. J. Blanchard, 1984). Second, the appearance of a high level of aggressive behavior requires that such colonies have repeated agonistic encounters with younger conspecific intruders Blanchard, Takahashi, & Blanchard, 1977;Williams, 1982). Finally, as was observed in Experiment 1, it is not unusual for both of the male residents of an aggressive colony to attack and bite the intruder (Williams & Lierle, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…There was also no effect of shock on subsequent agonistic behavior. Flannellyet al (1982) and Williams (1982) found that exposure to shock decreased subsequent aggression in mice and rats, respectively. However, Heller (1979) found increased agonistic behavior in mice that had been exposed to prior shock.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-four males, weighing between 400 and 500 g, served as experimental subjects. Males were approximately 130 days of age upon arrival; they were selected at this age because earlier findings had indicated that dominance is not established until about 140 days of age , 1984. Two males, weighing 500-600 g, served as aggressive residents, and 32 males, weighing 350-450 g, were used as intruders.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation